REFORMED IMMEDIATE PROCESS. THE DISCUSSION NEEDED - Araya Vega, Alfredo (2017)
The existence of early and timely resolution processes for matters of simple processing is now a reality. With the introduction of orality in judicial processes, the great challenge lies in obtaining true justice as a quality public service. What simple processes are solved in a differentiated way is not a problem, but a solution. The discussion now focuses on how to make it possible and what should be respected, beginning from the state criminal policy, the real reasons behind the reform, judicial guarantees and, finally, opportunities for improvement.